Injuries in Macedonia burden and postinjury impact. (1st March 2011) - Tozija, F; Dragan, G; Sethi, D; Nikovska, D Gudeva; Kasapinov, B; Sosolceva, M
Abstract : The aim of this paper is to assess the outcome and postinjury impact, analysing the data collected with the community-based injury survey conducted in Republic of Macedonia in 2008. WHO standard methodology has been applied on a nationally representative sample of 1200 households. The survey has recorded injury incidence rate of 5710/100 000 and mortality of 40/100 000. 75.2% of the reported injuries had not resulted in any physical disability. Most frequent physical disability is walk with a limp or difficulty using hand or arm; few reported inability to use hand or arm, loss of vision or inability to chew food. 46.4% of the victims were affected performing usual activities. 21.4% were not able to return to normal activities. Some of respondents stated losing their employment due to the injury. 31.2% reported losing days of work/school, on average 45 working days had been lost. There were also loss of work/school working days of a household member (7 days on average). 33.6% of injured reported decline in household income, while only one respondent stated a household member loss of employment due to taking care for the victim. This indicates that injuries and violence are serious public health problem that should be seriously considered for policy interventions. Prevention of injury and violence is set as on one of the priorities in the Health Strategy of the Republic of Macedonia 2008–2020.